Old South Meeting House, ca. 1880 - Unknown (Tufts Archival Research Center, 2005)
Elevated-view east of the Old South Meeting House, located on Washington Street at the northeast corner of Washington and Milk Streets. The facade of the church faces west-northwest towards Washington Street, while its south-southwest elevation lines Milk Street. Awnings and signage adorn the facades of buildings located on Washington Street to the northeast of the Old South Meeting House. Several pedestrians stand on the sidewalks lining both Washington and Milk Streets. The Boston Transcript Building, located at 324 Washington Street, is included along the right side of the photograph. Old South Meeting House built by Joshua Blanchard, 1729; Boston Transcript Building designed by Gridley J. Fox Bryant, 1873 3 3/4 x 5 5/8, 4 1/4 x 6 15/16 overall Stereographs